Nostalgica utopica futura / Luigi Nono at Stanford - Fusi, Marco; Bing Studio, Stanford University; Fusi, Marco (Stanford, CA (US) Center for Computer Research in Music and Acoustics, Stanford University, 2024)
In a special performance at Stanford University, Luigi Nono's La lontananza nostalgica utopica futura will be presented by violinist Marco Fusi and Patricia Alessandrini, who will perform the electronics. They will also perform their own homage to Nono, in the form of a brief improvised prelude, entitled Proximity, distance. This performance and its prelude were developed during a residency at the Curtis R. Priem Experimental Media and Performing Arts Center (EMPAC).
FRIS
0
Keywords: Nono, Luigi -- 1924-1990; HIPEX: Historical Performance Practices of Experimental Music; Electronic music